Improving ductility of a Mg alloy via non-basal slip induced by Ca addition. (September 2019) - Zhu, Gaoming; Wang, Leyun; Zhou, Hao; Wang, Jinhui; Shen, Yao; Tu, Peng; Zhu, Hong; Liu, Wei; Jin, Peipeng; Zeng, Xiaoqin
Abstract: Addition of a small amount of Ca improves the ductility of Mg alloys. However, the mechanism underlying this effect is not well understood. In this work, tensile testing of an extruded Mg−0.47 wt% Ca alloy was conducted inside a scanning electron microscope. Electron backscattered diffraction-based slip trace analysis was performed to study in-grain slip activities at 1%, 2%, 4%, 8%, and 16% tensile strain. While the majority of the grains were deformed by { 0001 } < 11 2 _ 0 > basal slip, slip lines from { 1 1 _ 00 } prismatic planes and { 1 1 _ 01 } pyramidal I planes were also frequently observed, and their fractions increased with strain. Ex situ transmission electron microscopy indicated that the pyramidal I slip lines were associated with dislocations instead of dislocations. From Schmid factor analysis, the critical resolved shear stresses of prismatic slip and pyramidal slip are approximately twice that of basal slip in this Mg–Ca alloy. The enhanced activity of non-basal slip improved the material's ductility. Our first-principles calculations found that solute Ca atoms would reduce the unstable stacking fault energy for all slip modes. Highlights: Mechanism of ductility enhancement in Mg by Ca alloying was investigated. Slip trace analysis showed different slip system activities at different strains. Ca addition was found to enhance the activity of non-basal slip. Influence of Ca on the GSFE curves of different slip systems was assessed.